Homophobia in Nigerian schools and universities: Victimization, Mental Health Issues, Resilience of the LGBT Students and support from Straight Allies. A Literature review - Okanlawon, Kehinde (Journal of LGBT youth, 2021)
This paper reviews the literature on the schooling experiences and challenges LGBT students face in Nigerian schools and universities, and how heterosexual students, teachers and school administrators view and respond to LGBT issues. Twenty-eight publications which include themes on LGBT experiences in Nigerian schools and universities were reviewed. Findings show that LGBT students experience rejection, bullying, and victimization from parents and siblings at home, and from students, teachers, and school administrators who sometimes expel LGBT students from schools and universities. The study shows internalized homophobia, stress and depression facing LGBT students, their resilience, and the support they receive from a few straight allies among students and lecturers. Findings reveal how Nigerian schools and universities promote compulsory heterosexuality through anti-gay views, disciplinary actions, and rules to discourage homosexuality. Finally, this paper discusses the implication of homophobia in Nigerian schools and universities and how to challenge homophobia regarding Nigeria's inclusive education goal.